Prinsip Nonintervensi dalam ASEAN Way: Menakar Kontribusi ASEAN dalam Resolusi Konflik di Myanmar - Windy Dermawan; Leony Gustaviani (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Southeast Asia is a region that is considered to have minimal conflict between countries, but on the other hand, the conflicts that arise tend to come from internal problems. In this case, on February 1 2021 the Myanmar military regime issued a coup statement on the Myanmar government. This of course creates a nightmare in society where the coup is considered to destroy people's daily activities. It didn't just stop there, the coup carried out by the military regime was also noted to have violated a number of human rights. In this case, the researcher seeks to highlight the effectiveness of ASEAN's role as a regional organization in efforts to resolve the coup that occurred in Myanmar through the perspective of the ASEAN Way which is based on the principle of non-intervention. Through qualitative method analysis using literature sources, the author tries to answer to what extent the ASEAN Way norms can resolve the conflict that occurred in Myanmar.